UPAYA MENINGKATKAN PEMBELAJARAN SEPAKBOLA DENGAN MEDIA GAWANG SIMPAI (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The problem from this research if holahoop can increase football learning for 5th grade SD kaligangsa 4 Tegaleducation year 2012/2013 while the aim from this research is to know how far holahoop media can increasefootball learning in 5th grade of SD Kaligangsa 4 Tegal education year 2012/2013. The research instrumen uselearning implementation observation paper, student’s motivation of study observation paper, student responsequestionnaire and practice test. The technique of data analysis is using descriptively and by counting a formulawhich has determined. The successfull of this research can said if the students get the completeness and theresult of student’s learning from cycle I to cycle II. The result which is get from learning football game is incognitive aspect, affective, and psychomotor with KKM 75 in first cycle only get average score 75,27 or around57,70% complete and still in category deficient, while in second cycle learning the result is getting better scorethat is 83,81 and be avowed all students has been completed.